Aplikasi Ensiklopedia Pakaian Adat Dunia Berbasis Android - Budi Permana; Eka Wahyu Hidayat; Alam Rahmatulloh (Politeknik Harapan Bersama, 2018)
The rapid development of technology and with the disruptive technology make multimedia developers continuously innovate in making specific information products. Internet as a source of information can be used as a reference to seek various information such as information about custom clothing from around the world. In addition to sources from the internet, many available information about custom clothing for example in print. The use of both media is found a variety of problems that Internet users must search for one by one information and readers should find information custom clothing one by one following details and explanations. The problem is solved by creating a digital encyclopedia about custom clothing in digital form based on multimedia technology using mobile application with Android operating system. The method for multimedia software engineering uses Luther method with its stages of concept, design, collecting material, assembly, testing, and distribution. The end result of this research in the form of multimedia products encyclopedia custom clothing in the form of android applications. Product test results have been passed using functionality testing and all functions can run well and in accordance with the concept. From the results of the survey on beta test results obtained 83% which states that the application is feasible to use.